PREPARATION AND RESEARCH OF HETEROSTRUCTURES GaP / Si BY PULSED LASER DEPOSITION - Oleg Devitsky; Igor Sysoev; Vitaliy Batishchev; Viktor Vasiliev; Ivan Kasyanov (Вестник Северо-Кавказского федерального университета)
Pulsed laser deposition method was heterostructure GaP / Si. The methods of reducing the magnitude of the mechanical stresses in the resulting film, Raman scattering found that using the method of pulsed laser deposition at 300 °C for heterostructure GaP / Si is possible to reduce the value of the mechanical stresses. Installed depth dependence of occurrence p-n transition in the heterostructure GaP / Si at different temperatures of the annealing time and also obtaining optimum parameters based heterostructure solar cell GaP / Si. Investigated the use of instrumentation GaP/Si heterostructures as a silicon solar cell c wide-window GaP. It is shown that the maximum open circuit voltage obtained solar cell reaches 900 mV at a value of the external quantum efficiency of about 74,5 %.